Kidney transplantation with allografts from infant donors—Small organs, big value. (5th August 2020) - Hoyer, Dieter Paul; Dittmann, Susanne; Büscher, Anja; Benkö, Tamas; Treckmann, Juergen Walter; Gallinat, Anja; Kribben, Andreas; Paul, Andreas; Hoyer, Peter Friedrich
Abstract: Background: Although infant organ donors remain a rare source of organs for transplantation, technical challenges have resulted in increased rates of complications and inferior graft function. The aim of the present study was to investigate the outcomes of kidneys procured from juvenile and infant donors. Patients and Methods: We evaluated all kidney transplants from deceased donors < 16 years of age performed at our center between 01/2008 and 08/2019. We defined three groups based on quartiles of donor body weight: <13 kg (infant donors), 13‐40 kg (juvenile donors), and > 40 kg (standard criteria donors). Clinical characteristics and outcomes were compared between groups. Results: Ninety‐two transplants were included in this study. Out of 92 recipients, there were 32 (34.8%) adult and 60 (65.2%) pediatric patients. All groups demonstrated excellent graft function and survival on both short and long‐term follow‐up. 1‐year, 3‐year, and 5‐year graft survival rates for the standard criteria donor group were 100%, 95.2%, and 88.4%, respectively, compared with 95.8% for infant and 95% for juvenile donors at all times ( P = .79). eGFR at 5 years was 98.9 ± 5.5, 74.1 ± 6.2, and 81.6 ± 6.9 mL/min/1.73 m 2 for infant, juvenile, and standard criteria donors, respectively ( P < .01). Conclusion: Infant donor allografts can be transplanted with excellent long‐term outcomes in both pediatric and adult recipients. Implanting them as single allografts onto pediatric candidates allows for the transplantation of two patients. As such, pediatric recipients should be prioritized for these donor organs.